Role of Trypanosoma cruzi Trans-sialidase on the escape from host immune surveillance - Nardy, Ana F. F. R. (2016)
Chagas disease is caused by the flagellate protozoan Trypanosoma cruzi, affecting millions of people throughout Latin America. The parasite dampens host immune response causing modifications in diverse lymphoid compartments, including the thymus. T. cruzi trans-sialidase (TS) seems to play a fundamental role in such immunopathological events. This unusual enzyme catalyses the transference of sialic acid molecules from host glycoconjugates to acceptor molecules placed on the parasite surface. TS activity mediates several biological effects leading to the subversion of host immune system, hence favoring both parasite survival and the establishment of chronic infection. This review summarizes current findings on the roles of TS in the immune response during T. cruzi infection.